Patents as a Driver of the Unprecedented Biomedical Response to COVID-19 - Adam Mossoff JD; Amesh Adalja MD (SAGE Publishing, 2022)
The response by the biotech and pharmaceutical sectors to the COVID-19 pandemic has been historically unprecedented. Vaccines based in cutting-edge technologies, such as the mRNA platform, were invented, tested, and distributed to patients in less than a year. Yet politicians and activists argue that patents and other intellectual property (IP) have impeded the development and distribution of these vaccines. In explaining why this is profoundly mistaken, this essay first describes the medical and economic uncertainties inherent in the production of vaccines, especially those made in response to an emerging infectious disease like COVID-19. This makes clear the unprecedented achievement in the mass production and distribution of COVID-19 vaccines in less than 1 year after the start of the COVID-19 pandemic. It then describes the current manufacturing and licensing landscape, which was created on the basis of a market infrastructure built by reliable and effective patent rights. There is now a glut in the global supply of vaccine doses-and billions more doses are still being produced. The essay concludes by identifying the non-IP causes impeding global vaccine distribution, such as lack of infrastructure in the developing world, as well as regulatory restrictions and trade barriers. Those concerned with global vaccine equity should focus on policies to resolve these real-world problems.